2019
DOI: 10.1038/s42256-019-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Shared human–robot proportional control of a dexterous myoelectric prosthesis

Abstract: Myoelectric prostheses allow users to recover lost functionality by controlling a robotic device with their remaining muscle activity. Such commercial devices can give users a high level of autonomy, but still do not approach the dexterity of the intact human hand. We present here a method to control a robotic hand, shared between user intention and robotic automation. The algorithm allows user-controlled movements when high dexterity is desired, but also assisted grasping when robustness is paramount. This co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 34 publications
0
84
0
1
Order By: Relevance
“…the redundancies that exist in both the central and peripheral nervous systems to guide motor control of a limb. If we could recruit a subset of these resources to train the user to control an external device using simplified operating principles (relative to the biological body), we could better benefit from already existing technological advancements [8].…”
Section: Recycling the Neural Basis Of The Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…the redundancies that exist in both the central and peripheral nervous systems to guide motor control of a limb. If we could recruit a subset of these resources to train the user to control an external device using simplified operating principles (relative to the biological body), we could better benefit from already existing technological advancements [8].…”
Section: Recycling the Neural Basis Of The Bodymentioning
confidence: 99%
“…Soft embodiment will also allow us to exploit sensorimotor resources without necessarily impacting bodily awareness and our sense of body ownership. This provides wider opportunities for implementation, such as with regard to currently emerging technologies for autonomous prosthesis control [8].…”
Section: Recycling the Neural Basis Of The Bodymentioning
confidence: 99%
“…To that end, many research groups, including us, have used multi-output regressionbased algorithms to map features extracted from surface or intramuscular EMG channels onto wrist [4][5][6][7][8] and/or finger position [9][10][11][12][13][14], velocity [15,16], and force trajectories [17][18][19][20]. For prosthetic digit control, several studies have shown premise in decoding position/velocity offline [9, 11-13, 15, 16], however, only a smaller number have achieved real-time digit control in amputees [10,14,21]. This indicates that, to date, reconstruction of position/velocity trajectories from surface EMG signals in real-time remains a challenging problem.…”
Section: Introductionmentioning
confidence: 99%
“…From a technical perspective, the ultimate goal of the myoelectric control field is to approximate this dexterity via simultaneous and independent control of multiple degrees of freedom (DOFs) in a continuous space. To that end, several groups, including us, have used regression-based methods to reconstruct wrist kinematic trajectories [11][12][13][14][15] , finger positions [16][17][18][19][20][21][22] and velocities 23,24 , as well as fingertip forces [25][26][27][28] . Only a few studies have, however, thus far demonstrated the feasibility of real-time prosthetic finger control in amputee users 17,21,22 .…”
mentioning
confidence: 99%